SLE Dengan Manifestasi Gangguan Ginjal Dan Nefritis Lupus - Wahyuni Wahyuni; Hayatul Farziani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Systemic Lupus Erythematosus is a chronic autoimmune inflammatory disease with a wide range of clinical manifestations and a diverse course and prognosis. Antibodies that are formed from the autoimmune process in SLE will damage the body's organs, causing tissue inflammation and severe blood vessel problems in almost all parts of the body, especially attacking the kidneys which cause health problems in the form of lupus nephritis. Lupus nephritis is usually asymptomatic with a variable clinical picture and occurs within the first few years after the onset of lupus. . Evaluation of kidney function is necessary to detect disease early. Kidney biopsy examination is recommended for every SLE patient, especially those showing symptoms of nephritis or kidney function tests that lead to nephritis.